The Effectiveness of Communication Messages in Politics - Kristomei Sianturi; Asti Megasari (Journal of Social Research, 2023)
As social creatures, every person who lives in a community group, in carrying out his daily activities from the time he wakes up in the morning until he goes back to sleep at night, is always involved in communication activities. This journal aims to find out how effective interpersonal communication messages are in a communication context. This journal uses types of research in the form of literature and reflective studies. Communication is said to be effective if what is communicated is understood and carried out by the communicant as desired by the communicator. Barriers to the communication process, small obstacles may be ignored, but too many obstacles can disrupt or disrupt the message from achieving its goal. The effectiveness of communication in politics is very important because it can influence the success of a government program or policy. Effective political communication can increase public participation in the political process.